PENGARUH ADMINISTRASI KESISWAAN TERHADAP KEPUASAN SISWA - Sida, Syarifuddin C.N. (Makassar Journal of Social Sciences, 2015)
This study aims to determine the effect of Student Administration Student Satisfaction In SMKN 5 Bantaeng Bantaeng. This research uses descriptive quantitative research population is all students of class XI IPS IPS. Data collection is done by means of questionnaires, interviews, observation, and documentation. Data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results showed that the administration student at SMK 5 Bantaeng Bantaeng classified in the category very well, in terms of the good aspects of administrative management and the ability of employees in performing their duties. The level of student satisfaction SMKN 5 Bantaeng Bantaeng classified in the category very good in terms of performance and service provided by the employee. Hypothesis testing results indicate that there is significant influence between the administration of student with student satisfaction SMKN 5 Bantaeng Bantaeng. It can be seen from the results of data analysis has been conducted, and the results showed that the level of influence belonging to the category is strong enough.